2023
DOI: 10.3390/ijms241512367
|View full text |Cite
|
Sign up to set email alerts
|

Coffea arabica Extract Attenuates Atopic Dermatitis-like Skin Lesions by Regulating NLRP3 Inflammasome Expression and Skin Barrier Functions

Abstract: Atopic dermatitis (AD) is a common skin disease worldwide. The major causes of AD are skin barrier defects, immune dysfunction, and oxidative stress. In this study, we investigated the anti-oxidation and anti-inflammation effects of Coffea arabica extract (CAE) and its regulation of the skin barrier and immune functions in AD. In vitro experiments revealed that CAE decreased the reactive oxygen species levels and inhibited the translocation of nuclear factor-κB (NF-κB), further reducing the secretion of interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Consistent with the vast majority of recent research reports, NLRP3 expression is up-regulated in AD, and repressing NLRP3 activation can mitigate AD. 58,[60][61][62][63][64] A previous study has also indicated that one of the possible anti-inflammatory mechanisms of CQ is repression of the NLRP3 inflammasome activity. 34 The antimalarial CQ reduces LPS-induced activation of the NLRP3 inflammasomes, thereby conferring protection against murine endotoxic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the vast majority of recent research reports, NLRP3 expression is up-regulated in AD, and repressing NLRP3 activation can mitigate AD. 58,[60][61][62][63][64] A previous study has also indicated that one of the possible anti-inflammatory mechanisms of CQ is repression of the NLRP3 inflammasome activity. 34 The antimalarial CQ reduces LPS-induced activation of the NLRP3 inflammasomes, thereby conferring protection against murine endotoxic shock.…”
Section: Discussionmentioning
confidence: 99%
“…The chlorogenic acid and caffeic acid present in Coffea arabica extract (CAE) have been shown to have antioxidant activity both in vitro and in vivo. In vitro CAE treatment results in reduced levels of IFN-γ/TNF-α-induced intracellular ROS and increased levels of antioxidant enzymes such as CAT, thereby improving the balance between oxidant and antioxidant factors at the skin level [100]. In vivo, caffeic acid not only improves AD lesions, by reducing TEWL and restoring the skin barrier and IVL, FLG, and LOR, but also gives the best results in terms of scavenging free radicals and inhibiting lipid peroxidation [101].…”
Section: Flavonoidsmentioning
confidence: 99%